Biocontrol potential of Moringa leaf extract on fungi causing postharvest deterioration of maize (Zea mays L.) seeds during storage in Makurdi - Liamngee, K; Adams, A; Zakki, Y H; Manguts, Y; Amon, T E (Journal of Postharvest Technology, 2019)
Maize (Zea mays L.) is an important cereal crop ranked second to wheat and a source of protein and energy in human diets throughout the world. The biocontrol potential of Moringa leaf extract on fungi causing deterioration of maize seeds in storage was carried out. The fungi were isolated using standard blotter method and Moringa leaf extract at concentrations of 25, 50, 75 and 100%w/v were used to inhibit the growth of the fungi from the maize seeds both in vitro and in vivo. Four species of fungi namely; Rhizopus stolonifer, Aspergillus flavus, Aspergillus niger and Curvularia affinis were isolated from the maize seeds. There was no significant difference in percentage occurrence of Rhizopus stolonifer across the markets (P>0.05). For Aspergillus flavus, High Level market recorded significantly higher (P<0.05) occurrence (18.90) compared with Wadata market (0.00) which had the lowest incidence. However, there was significant difference between Wadata and High Level markets. For Aspergillus niger and Curvularia affinis, there was no significant difference across the four markets (P>0.05). For seed germination, Wadata market recorded the highest (98.90) while Wurukum reported the lowest (41.20).In the biocontrol experiment, all extract concentrations inhibited the growth of the different fungi at varying degrees with 100%w/v showing significantly higher inhibition compared to all other concentrations. The relatively high prevalence of Aspergillus niger on the maize seeds points to the possibility of aflatoxin contamination. Application of Moringa leaf extract inhibits greatly the growth of fungi on maize seeds and the degree of inhibition increases with increasing concentration.